VD_FINDINFO MP / 2016 / 7 vom 16. Dezember 2016 - VD Tribunal cantonal (2016)
MESURE PROVISIONNELLE, INTÉGRITÉ DE L'OEUVRE, ARCHITECTURE, TRANSFERTEN GÉNÉRAL | 1 al. 1 LDA, 11 LDA, 2 al. 1 LDA, 65 LDA, 261 CPC (CH), 262 CPC (CH), 5 al. 1 let. a CPC (CH)